Single stars in the Hyades open cluster: fiducial sequence for testing stellar and atmospheric models - Kopytova, Taisiya G.; Röser, Siegfried; Schilbach, Elena (Arxiv, 2015)
Age and mass determinations for isolated stellar objects remain model-dependent. While stellar interior and atmospheric theoretical models are rapidly evolving, we need a powerful tool to test them. Open clusters are good candidates for this role. We complement previous studies on the Hyades multiplicity by Lucky Imaging observations with the AstraLux Norte camera. This allows us to exclude possible binary and multiple systems with companions outside 2--7 AU separation and to create a "single-star sequence" for the Hyades. The sequence encompasses 250 main-sequence stars ranging from A5V to M6V. Using the "Tool for Astrophysical Data Analysis" (TA-DA), we create various theoretical isochrones applying different combinations of interior and atmospheric models. We compare the isochrones with the observed Hyades single-star sequence on J vs. J - K_s, J vs. J - H and K_s vs. H - K_s color-magnitude diagrams. As a reference we also compute absolute fluxes and magnitudes for all stars from X-ray to mid-infrared based on photometric measurements available in the literature(ROSAT X-ray, GALEX UV, APASS gri, 2MASS JHK_s, and WISE W1 to W).We find that combinations of both PISA and DARTMOUTH stellar interior models with BT-Settl 2010 atmospheric models describe the observed sequence well. The full sequence covers the mass range 0.13 to 2.3 Msun, and effective temperatures between 3060 K and 8200 K. Within the measurement uncertainties, the current generation of models agree well with the single-star sequence. The primary limitations are the uncertainties in the measurement of the distance to individual Hyades members, and uncertainties in the photometry. Additionally, a small (~0.05 mag) systematic offset can be noted on J vs. J - K and K vs. H - K diagrams - the observed sequence is shifted to redder colors from the theoretical predictions.